Immunotherapy for Hepatocellular Carcinoma: Current Limits and Prospects - Zhong, Cheng; Li, Yirun; Yang, Jing; Jin, Shengxi; Chen, Guoqiao; Li, Duguang; Fan, Xiaoxiao; Lin, Hui (Frontiers in Oncology, 2021)
Although many approaches have been used to treat hepatocellular carcinoma (HCC), the clinical benefits remain limited, particularly for late stage HCC. In recent years, studies have focused on immunotherapy for HCC. Immunotherapies have shown promising clinical outcomes in several types of cancers and potential therapeutic effects for advanced HCC. In this review, we summarize the immune tolerance and immunotherapeutic strategies for HCC as well as the main challenges of current therapeutic approaches. We also present alternative strategies for overcoming these limitations.